(untitled) (Research, Society and Development, 2022)
The population growth of the elderly is a global reality. Allied to this, the need for greater attention to the health of this group and all the biopsychosocial aspects inherent to it increases, and therefore their sexuality should not be neglected. Thus, it was aimed to analyze the perception of the elderly to preventive measures for sexually transmitted infections. This is an integrative literature review. The literature search was developed in the Virtual Health Library (BVS-BIREME), through the databases: SciELO, Lilacs, BDENF and MEDLINE. Using the following descriptors combined with the Boolean operator AND, namely: "HIV Infection" AND "Elderly Health" AND "Sexuality". Articles written in Portuguese or English, freely available in full, from January 2016 to December 2021 were included. Studies published in annals, monographs, dissertations, and theses that were not available in full for free were excluded. Thus, the sample was composed of 12 articles. The results indicate that the elderly have little knowledge about preventive methods, experience their sexuality and consider condom use as something related to younger people, therefore, the stigmas and social taboos about the sexual life of this part of the population still prevail in the social imaginary. Thus, even after the age of 60 it is still possible to live all the spheres of life with quality. In this sense, it establishes the important role of health professionals through education and promotion of quality of life, resulting in greater autonomy of the elderly to decide on actions that promote the increase of their well-being.